49–2ax –a^2–x^2
Extract the negative sign
= 49 - (a^2 +2ax +x^2)
Factor using a^2 + 2ab + b^2 = (a+b)^2
= 49 - (a+x)^2
Factor using a^2 - b^2 = (a-b)(a+b)
= ( 7- (a + x)) * (7 + (a + x))
= ( 7- a - x) * (7 + a + x)
Answer:
What is the simplified form of this expression?
7a2 + 10a − 3a − 2a2
Step-by-step explanation:
7a2 + 10a − 3a − 2a2
Combine like terms
742 + 10a - 3a - 2a2
742 + 7a - 2a2
solution=
5a2 + 7a
Based on the reflexive property of congruency, the missing step in the proof is: A. ∠ABC ≅ ∠DBE
<h3>What is the
Reflexive Property of Congruency?</h3>
The reflexive property of congruency states that an angle will always be congruent to itself.
In the diagram given, we can prove that ∠ABC ≅ ∠DBE based on the reflexive property.
Therefore, the missing step in nthe proof is: A. ∠ABC ≅ ∠DBE
Learn more about reflexive property on:
brainly.com/question/1601404
#SPJ4
Answer:
Step-by-step explanation:
3x+2x+7=22
5x+7-7=22-7
5x=15
5x/5=15/5
X=3
Answer:
Irrational
Step-by-step explanation:
I hoped this helped, I don't know if it's right